Subyektivitas Penafsiran “Biarawan” Imam Zamakhsyari Terhadap Anjuran Menikah Dalam Al-Qur’an - Fajri Kamil; Risan Rusli (Jurnal Semiotika Quran, 2023)
The purpose of this research is to discuss the subjective interpretation of "monastic" by Imam Zamakhsyari regarding the recommendation of marriage in the Quran. This study falls under the category of qualitative research; hence, the researcher solely conducts a literature review. The research employs an interpretative approach and a historical approach. The primary data source for this research is the book "Tafsir al-Kasysyaf," supplemented by secondary data from literary sources. The discussion and findings of this research reveal that when faced with verses that emphasize the recommendation of marriage, such as Surah Al-Rum/30 verse 21, Surah Al-Nisa/4 verse 3, and Surah An-Nur/24 verse 32, both implicitly and explicitly, there are influences on his position as a scholar who chooses to live as a "monk." There is a specific stance that represents his life choice of not marrying, influenced by affective history. There exists a pre-understanding that constitutes Imam Zamakhsyari's initial position, which he engages in dialogue with the Quranic text and can be criticized for not aligning with the intended meaning of the interpreted text. The influence of affective history and the position of hermeneutical pre-understanding can be observed in his verses, expressing a profound reflection on his decision not to marry.